2014
DOI: 10.4103/0973-1482.136678
|View full text |Cite
|
Sign up to set email alerts
|

Malignant fibrous histiocytoma of maxillary alveolar ridge extending to the hard palate

Abstract: Malignant fibrous histiocytoma (MFH) is the most common soft-tissue sarcoma occurring in adults. This entity was first described by O'Brian and Stout in 1964. Apart from the soft-tissues, this tumor has been reported to occur in all other parts of the body including bone. It has male predilection and is usually noticed in the fifth to seventh decades of life. It commonly affects extremities and retroperitoneum, whereas involvement of the head and neck region is comparatively rare. However, when the head and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…[ 3 ] The second school of thought is along the lines of mesenchymal stem cell transformation. [ 4 5 ] Both these postulates need to be extensively researched for which many such cases of UPS need to be analyzed in detail.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] The second school of thought is along the lines of mesenchymal stem cell transformation. [ 4 5 ] Both these postulates need to be extensively researched for which many such cases of UPS need to be analyzed in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Some cases may reveal extensive inflammatory infiltrate and pres- Table 1. Clinicopathological features of undifferentiated pleomorphic sarcoma in cases retrieved from the PubMed database 4,5,8,11,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] ence of an evident multinucleated giant cell component 18,19 . We believe that this microscopic finding along with inadequate sampling of the lesion led to the initial misdiagnosis of a central giant cell lesion in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…To date, although some articles have discussed the sonographic features of malignant fibrous histiocytoma developing in the chest wall, breast, kidney, maxillary alveolar ridge, and intestines, the sonographic features of malignant fibrous histiocytoma of the thyroid have only been reported for 2 cases. Malandrinou et al reported a 2.5 × 1.6‐cm mass with mixed echogenicity, adenomalike morphologic characteristics, cystic degeneration, and hemorrhagic necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…A previous article suggested that the absence of suspicious malignant sonographic features, when all nodules are 4 cm or larger, does not effectively exclude malignancy, and the incidence of clinically important thyroid cancer within a nodule of 4 cm or larger is 22%. 12 To date, although some articles have discussed the sonographic features of malignant fibrous histiocytoma developing in the chest wall, breast, kidney, maxillary alveolar ridge, and intestines, [13][14][15][16][17] the sonographic features of malignant fibrous histiocytoma of the thyroid have only been reported for 2 cases. Malandrinou et al 3 reported a 2.5 3 1.6-cm mass with mixed echogenicity, adenomalike morphologic characteristics, cystic degeneration, and hemorrhagic necrosis.…”
Section: Discussionmentioning
confidence: 99%